Alcalóides ciclopeptídicos da espécie Discaria americana gilles and hooker: estereoquímica e atividade antimicrobiana - Dahmer, Janice (2013)
The purpose of this study was to conduct a phytochemical study of the crude extract of the root bark of the species Discaria americana Gilles and Hooker. The origin of this knowledge has been proposed the use of this plant in popular medicine for the treatment of various diseases such as fever, skin diseases, stomach disorders, diabetes and as a tonic in the form of teas and infusions. Through this study was isolated six compounds among which four are cyclopeptide alkaloids, one cyclopeptide alkaloid neutral and one triterpenoid. Cyclopeptide alkaloids isolated are known as Discarine B (23) C Discarine (44) Frangufoline (26) and Frangulanine (27). The cyclopeptide alkaloid neutral is known as Discarene C (63) and triterpenoid is known as Betulinic Acid (69). In this study it was possible to determine the absolute configuration of the compound Discarine C (44) by X-ray diffraction and derivatisation of the amino acids present in the molecule, which were subjected to enantiosselective gas chromatography. Still in phytochemical analysis, we determined the significant activity of some of the isolated compounds. The alkaloid ciclopeptídico Discarine B (23), Discarine C (44), Frangulanine (27) and cyclopeptide alkaloid neutral Discarene C (63) proved strong bacteriostatic against the strain Salmonella typhimurium being the Discarine C (44) showed strong potential bactericidal front of this strain. Discarine B (23) showed significant potential bacteriostatic and bactericidal against the Enterococcus spp and appreciable potential bacteriostatic front Escherechia coli. It was possible to establish a relationship between their structure and configuration and its antimicrobial activity.